Development of simple and cost-effective treatment system for municipal wastewater - Takashi Onodera; Kazuaki Syutsubo (Syiah Kuala University, 2015)
This study developed an alternative municipal sewage treatment system based on the pilot- and full-scale experiments. This proposed system consisting of upflow anaerobic sludge blanket (UASB) and trickling filter using a polyurethane sponge as packing material. This aerobic process was originally developed and named as a down-flow hanging sponge (DHS). DHS reactors accomplished high process performance during pilot- and full-scale experiments in Japan and other countries. The effluent quality of the DHS reactors was comparable to that of activated sludge systems. Moreover, advantages of DHS reactors include simple operation and maintenance (OM), no required oxygen supply, small land requirement, and less excess sludge production. Indeed, the estimated energy requirement and excess sludge production of UASB and DHS systems were found to be approximately 75 and 85 % lower than those of conventional activated sludge systems, respectively. The high process performance can be attributed to the fact that the DHS reactor maintains much of the sludge in the reactor at concentrations 5–10 times higher than activated sludge. This indicates that DHS reactors have the potential for use as reliable, affordable, and efficient treatment systems, and can be used widely including developing countries.